The Merit of Using Experts or Consumers as Members of Planning Groups: A Field Experiment in Health Planning - Nutt, Paul C. (Academy of Management Journal, 1976)
A field experiment is described which compared the innovativeness and quality of solutions from health planning groups made up of health services users??activists? or professional consumers?and experts?physicians, nurses, administrators, and therapists. The experimental findings suggest several guides for planning.